2023
DOI: 10.1111/1753-0407.13441
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to thyroid hormone and risk of components of metabolic syndrome in a Chinese euthyroid population

Abstract: IntroductionTo evaluate the association of sensitivity to thyroid hormone with metabolic syndrome (MetS) and its components in a Chinese euthyroid population.MethodsA total of 3573 participants from Pinggu Metabolic Disease Study were analyzed. Serum‐free triiodothyronine (FT3), free thyroxine (FT4), thyrotropin (TSH), total adipose tissue (TAT), visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT) area of abdominal, and lumbar skeletal muscle area (SMA) were measured. Central thyroid hormone resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Another study confirmed that TFQI was the indicator of resistance to thyroid hormones and was associated with diabetes and hypertension in euthyroid Tehranian populations [41]. Recently, emerging studies investigated the relationship between sensitivity to thyroid hormones, metabolic disorders, and non-alcoholic fatty liver disease in Chinese subjects [18][19][20]42]. However, the influencing factors of thyroid hormone sensitivity is unclear.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study confirmed that TFQI was the indicator of resistance to thyroid hormones and was associated with diabetes and hypertension in euthyroid Tehranian populations [41]. Recently, emerging studies investigated the relationship between sensitivity to thyroid hormones, metabolic disorders, and non-alcoholic fatty liver disease in Chinese subjects [18][19][20]42]. However, the influencing factors of thyroid hormone sensitivity is unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, Teng et al demonstrated that impaired sensitivity to thyroid hormones was related to higher risks of cardiovascular disease and hyperuricemia and a lower risk of obesity in patients with subclinical hypothyroidism [18]. Recently, the association of impaired sensitivity to thyroid hormones with high levels of homocysteine [17], components of metabolic syndrome [19], and non-alcoholic fatty liver disease [20] were also revealed. However, the influencing factors of sensitivity to thyroid hormones and whether vitamin D deficiency is correlated with reduced sensitivity to thyroid hormones are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, TSHI and TT4RI were not ( 20 ). One possible reason may be that TFQI FT4 is more stable than TT4RI and TSHI, as it does not reach extreme values ( 20 ), indicating that the mechanisms of resistance to thyroid hormones were complex and challenging ( 40 ). Previous studies have made it clear that low T3 syndrome is associated with death.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by mutations in the thyroid hormone receptor beta (THRB) gene, which modulates the negative regulation of the HPT axis ( 41 ). RTH ( 40 ) is characterized by elevated serum TH levels without TSH suppression. In contrast, these individuals exhibit symptoms of thyrotoxicosis in other tissues that typically express TRα1 predominantly, such as the heart, bone, muscle, and adipose tissue, leading to various metabolic disorders ( 25 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some patients who are euthyroid and don’t have a history of thyroid disease might still be at risk of developing dyslipidemia due to impaired sensitivity to thyroid hormones. A study on 3573 euthyroid participants has shown that reduced thyroid hormone sensitivity is associated with metabolic syndrome and some alterations in lipoproteins, mainly TG ( 12 ).…”
Section: Thyroidmentioning
confidence: 99%